LANGUAGE ANXIETY OF ENGLISH AS A FOREIGN LANGUAGE AS PERCEIVED BY LEARNERS IN VOCATIONAL SCHOOL - Agung Gianjar Anjaniputra (Universitas Suryakancana, 2018)
Given that one of the difficulties in a foreign language acquisition associated with affects is anxiety that is undergone in different circumstances, and may determine the success of acquiring second/foreign languages, this research is aimed at portraying the situations under which learners undergo anxiety in EFL classroom and at exploring how learners cope with their anxiety by involving six students in a vocational school. Under the umbrella of descriptive research, interviews were conducted to collect the data required to address the purposes of this research. The result revealed that the situations under which learners experience language anxiety were categorized into two types of situation that entail performing in front of others and being pointed out by the teacher. Moreover, strategies to cope with the anxiety comprised preparation, positive thinking, and relaxation. Thus, it is suggested that teachers alleviate language anxiety by means of providing sufficient time for preparation, and creating friendlier classroom environment to avoid humiliating learners so that learners’ second/foreign language acquisition and learning are optimized.